A study on the effects of organoclay content and compatibilizer addition on the properties of biodegradable poly(butylene succinate) nanocomposites under natural weathering. (April 2015) - Phua, Yi Jing; Lau, Nyok-Sean; Sudesh, Kumar; Chow, Wen Shyang; Ishak, ZA Mohd.
Biodegradable poly(butylene succinate)/organo-montmorillonite nanocomposites were prepared at different organo-montmorillonite loadings, using maleic anhydride-grafted poly(butylene succinate) as compatibilizer. Poly(butylene succinate) nanocomposites were exposed to outdoor natural weathering for 180 days. Weight loss and decrease in mechanical properties after weathering revealed the degradation of poly(butylene succinate). Natural weathering caused photo-oxidation on poly(butylene succinate), leading to the formation of degraded products, as manifested in Fourier transform infrared spectroscopy. Gel permeation chromatography showed a significant reduction in molecular weight after weathering. It was noted that poly(butylene succinate) nanocomposite exhibited lower degradability as compared to neat poly(butylene succinate), due to the enhanced barrier properties after the addition of organo-montmorillonite. However, the incorporation of maleic anhydride-grafted poly(butylene succinate) increased the degradability. Degree of crystallinity of poly(butylene succinate) reduced after weathering, as shown in differential scanning calorimetry. Scanning electron microscopy analysis revealed fungal and bacterial colonization on the sample surface. In addition, the isolation and identification of bacterial strain were also performed.